Resolving the gas diffusion layer substrate land and channel region contributions to the oxygen transport resistance of a partially-saturated substrate. (20th December 2019) - Ge, N.; Shrestha, P.; Balakrishnan, M.; Ouellette, D.; Wong, A.K.C.; Liu, H.; Lee, CH.; Lee, J.K.; Bazylak, A.
Abstract: A novel analytical model was derived for the first time to predict the substrate oxygen transport resistance as a function of local saturations in the substrate region under the channel (region C) and the substrate region under the land (region L). Prior to this work, the state-of-the-art was limited to correlating bulk substrate oxygen transport resistance to bulk liquid water saturation in the GDL substrate. In this work, a semi-empirical approach was taken whereby the exponents m and n for calculating the effective diffusivity and the effective diffusion distance in region L were determined through a calibration process with experimentally measured saturations and calculated substrate oxygen transport resistance. The distinct relationships between local saturation and effective diffusivity for region C and region L were elucidated from the model. Via the model, it was determined that the local saturation in region C had an up to 2.8 times higher impact on the substrate oxygen transport resistance than the local saturation in region L. The oxygen transport resistance analysis was further supported by experimentally measured mass transport resistance of the fuel cell. The rise of saturation in region C led to a significant increase in the mass transport resistance; in contrast, increasing saturation in region L had a relatively lower impact on the mass transport resistance. Highlights: Oxygen transport resistance is a modeled as a function of local saturations. Oxygen transport resistance is dominated by saturation in substrate channel region. Rising saturation in substrate channel region causes significant performance loss.